A molluscan TNF receptor-associated factor 2 (TRAF2) was involved in host defense against immune challenges. Issue 71 (December 2017) - Qu, Fufa; Xiang, Zhiming; Zhou, Yingli; Qin, Yanping
Abstract: Tumor necrosis factor (TNF) receptor-associated factor 2 (TRAF2) is a member of the TRAF superfamily that acted as a key signal transduction protein and has been implicated in inflammatory and apoptosis processes in mammals. However, identification of TRAF2s in invertebrates is very limited and its function, in particular that under immune challenges, is still unknown. In this report, a molluscan TRAF2 gene (referred to as Aw TRAF2) was cloned and characterized from the freshwater bivalve, Anodonta woodiana . The open reading frame (ORF) of Aw TRAF2 was 1683 bp in length, which encoded a putative 560 amino acid-protein. The deduced Aw TRAF2 sequence shared similar structural characteristics and close evolutionary relationship with mollusk TRAF2s. The tissue-specific expression analysis revealed that Aw TRAF2 mRNA was broadly expressed in all tested tissues, with high expression in gill and hepatopancreas. In addition, in vivo injection experiments directly showed that Aw TRAF2 mRNA levels in hepatopancreas were significantly up-regulated in response to bacterial pathogen ( Vibrio alginolyticus and Staphylococcus aureus ) and PAMPs (Lipopolysaccharides and Peptidoglycan) challenges. Moreover, fluorescence microscopy observations revealed that Aw TRAF2 was mainly located in cytoplasm of HEK293T cells and its overexpression significantly increased the transcriptional activities of the NF-κB-Luc reporter gene in HEK293T cells. Taken together, this study provided the experimental evidence of the presence of a functional TRAF2 in freshwater bivalves, which revealed its involvement in host response to immune challenges in A. woodiana . Highlights: The first experimental evidence for presence of TRAF2 gene in freshwater bivalves. Aw TRAF2 mRNA was ubiquitously expressed in all selected adult tissues. Aw TRAF2 transcript levels could be significantly up-regulated by immune challenges. Aw TRAF2 was localized in cytoplasm and activated NF-κB-Luc in HEK293T cells.